La convention du travail maritime et le marin connecté - Arnaud Le Marchand (Netcom)
Seafarers stayed paradoxically, distant from ICT, mobile and internet phone. This situation begins to change, while a new international convention of the maritime labor comes into effect. The hybridization between internet and international conventions can result in a new regulation of a labor market. But this cyberpolitics is still very virtual. The connected seafarer allow to put in light the process of construction of internet at sea, as a market and the links to the need of internet to organize new social regulations of maritime labor.